Combine Improvement for Dye-Sensitized Solar Cells: Characterization of Metal Oxide-Doped TiO2 Nanoparticles Integrated with Clitoria Ternatea Extract - Ronaldo; Rusdianasari; Hasan, Abu (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Dye Sensitized-Solar Cells (DSSC) represent a third-generation solar cell technology based on photoelectrochemical principles. This study explores the use of Clitoria ternatea (butterfly pea) extract as an organic dye for DSSCs, focusing on its ability to absorb sunlight effectively. Excitation of electrons triggered by light in photocatalysis is strongly influenced by the position of the band gap. To be effective as a photocatalyst, the material must have a conduction band with a high positive potential compared to the electron accepting potential. Doping metal oxides such as CuO, MgO, Fe2O3, and ZnO into TiO2 can change the band edge properties or surface states which can increase light absorption. This research presents the synthesis of TiO2 nanoparticles as photoanodes doped using metal oxides to evaluate characteristic that can influence DSSC performance. TiO2 nanoparticles doped with metal oxide were synthesized using the solvothermal method and characterized by XRD, SEM-EDX, FTIR, and UV-Vis. Comprehensive analysis of samples doped with metal oxides significantly affects the crystal structure, morphology, elemental composition, and optical properties of the material. The results showed that Cu-doped TiO2 samples allowed for the most significant performance improvement in DSSC, followed by Fe-doped TiO2, Mg-doped TiO2, and Zn-doped TiO2, with pure TiO2 having the lowest performance potential. These results provide important insights into material optimization to improve DSSC efficiency.